Optogenetics-Mediated Targeted Recording from Adult-Born Granule Cells in the Dentate Gyrus of Behaving Mice - Yang, Ming (2017)
The aim of the study is to develop a new recording method to overcome the difficulty in determining cellular identity of neurons generating recorded activity in traditional electrophysiological extracellular recording which will help to investigate the properties of adult-born granule cell which is thought to be related to memory formation and learning. [1st Award]